2015
DOI: 10.1177/0269216315607180
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the feasibility study: Lessons from a study of the hand-held fan used to relieve dyspnea in people who are breathless at rest

Abstract: Feasibility work is essential, even for simple widely employed interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 19 publications
1
54
0
Order By: Relevance
“…A recent systematic review6 included a meta-analysis of fan at rest which showed improved subjectively reported breathlessness 6. An observational feasibility study that showed approximately half of the participants with breathlessness at rest gained a benefit from fan use that persists until further exertion 7. In a feasibility randomised controlled trial (RCT), more participants still used the fan for breathlessness after 2 months than those in the control intervention 8.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review6 included a meta-analysis of fan at rest which showed improved subjectively reported breathlessness 6. An observational feasibility study that showed approximately half of the participants with breathlessness at rest gained a benefit from fan use that persists until further exertion 7. In a feasibility randomised controlled trial (RCT), more participants still used the fan for breathlessness after 2 months than those in the control intervention 8.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for using 5 minutes of directed airflow was based on previous studies that achieved symptom palliation with this duration. [30][31][32] Like previous studies, the distance, location, side of face, strength, and swing of the fan was determined as per the patient's preference. 30,31 A standing fan placed on the floor was initially turned on at the lowest speed and was gradually adjusted to increase the speed and strength of the fan breeze.…”
Section: Interventions and Proceduresmentioning
confidence: 99%
“…[30][31][32] Like previous studies, the distance, location, side of face, strength, and swing of the fan was determined as per the patient's preference. 30,31 A standing fan placed on the floor was initially turned on at the lowest speed and was gradually adjusted to increase the speed and strength of the fan breeze. In the control arm, airflow was directed unto the legs with the patient's skin exposed for 5 minutes using the same model of the fan as that used in the intervention arm.…”
Section: Interventions and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…By providing a steady airflow that cools down the surface temperature of the skin, fan-on-face therapy creates an environment which may optimize the breathing conditions of terminally-ill cancer patients. 20 Lastly, because of its uncomplicated nature, fanon-face therapy is generally safe, and gives patients and their caregivers the opportunity to actively and effectively manage dyspnea during the end of life.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%